The Routledge handbook of disability activism - Berghs, Maria; Chataika, Tsitsi; El-Lahib, Yahya; Dube, Andrew K. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The onslaught of neoliberalism, austerity measures and cuts, impact of climate change, protracted conflicts and ongoing refugee crisis, rise of far right and populist movements have all negatively impacted on disability. Yet, disabled people and their allies are fighting back and we urgently need to understand how, where and what they are doing, what they feel their challenges are and what their future needs will be. This comprehensive handbook emphasizes the importance of everyday disability activism and how activists across the world bring together a wide range of activism tactics and strategies. It also challenges the activist movements, transnational and emancipatory politics, as well as providing future directions for disability activism. With contributions from senior and emerging disability activists, academics, students and practitioners from around the globe, this handbook covers the following broad themes: Contextualising disability activism in global activism Neoliberalism and austerity in the global North Rights, embodied resistance and disability activism Belonging, identity and values: how to create diverse coalitions for rights Reclaiming social positions, places and spaces Social media, support and activism Campus activism in higher education Inclusive pedagogies, evidence and activist practices Enabling human rights and policy Challenges facing disability activism The Routledge Handbook of Disability Activism provides disability activists, students, academics, practitioners, development partners and policy makers with an authoritative framework for disability activism"--
OCLC-licensed vendor bibliographic record.
Keywords: People with disabilities -- Political activity; People with disabilities -- Civil rights; Discrimination against people with disabilities; POLITICAL SCIENCE / General; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Social Work